Internationalisation of emerging markets MNC’s and SME’s: A Study of Indian Firms - Sabharwal, Naman (2016)
Internationalisation of MNC’s and SME’s is the basic context of this paper. This is a qualitative multiple-case study based on the Internationalisation of the MNC’s and SME’s from the emerging economy, India. The paper aims to identify the motives, capabilities and model of the internationalisation of MNC’s and SME’s from India. A comparative analysis is thereby used to address the differences and similarities between the internationalisation process of these MNC’s and SME’s. Although the research content on the internationalisation of the MNC’s and the SME’s is increasing lately, but there is hardly any research that involves the comparisons of internationalisation process of the MNC’s and SME’s. The firms chosen for study are two major MNC’s and two Born Global SME’s operating from India. The previous theories and literatures are used for relating with the actual internationalisation process of these firms considered. The finding illustrates the significant differences in the motives and capabilities involved in the internationalisation between the SME’s and MNC’s. The MNC’s were observed to have strong motives in order to seek potential market, resources and strategic assets and had strong firm specific advantages during internationalisation. While, the motives of SME’s came from the attitudes, knowledge and networks of the founders/managers and these SME’s had limited capabilities owing to their liability of smallness. . However, the firms of both the segment exploited the home country advantage in order to overcome their competitions. Both the segments of firms were observed to follow different model of internationalisation. For MNC’s, there strong firms-specific advantages helped them to overcome their limitation in terms of internationalizing from emerging economy. For SME it was observed that the networks were the major catalyst in their entire process of internationalisation. Moreover, the SME’s were found to have a high flexibility and quick adaptation to change.